IMPLEMENTATION OF HEALTH EDUCATION ON DIABETES FOOT EXERCISES USING BOOKLET MEDIA FOR A DIABETES MELLITUS SUFFERER IN KARANGTURI VILLAGE BANYUMAS REGENCY: CASE REPORT - Lusi Setiawati; Nuriya Nuriya; Ridlwan Kamaluddin; Agis Taufik (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Introduction: Diabetes mellitus is also known as a